Assessing Urban Quality of Life: Developing the Criteria for Saudi Cities - Al-Qawasmi, Jamal; Saeed, Muhammad; Asfour, Omar S.; Aldosary, Adel S. (Frontiers in Built Environment, 2021)
Urban quality of life (QOL) is a complex and multidimensional concept. A wide range of urban QOL assessment tools have been developed worldwide to measure and monitor quality of urban life taking into account the particular conditions of cities/regions and the needs of their residents. This paper aims to develop an urban QOL assessment tool appropriate for the context of Saudi Arabia (SA). For this purpose, the paper developed and used a structured approach consists of in-depth analysis of 21 urban QOL assessment tools in use worldwide, combined with focus group analysis and feedback from Panel of Experts. The results revealed that there is lack of consensus among existing tools regarding the usage of QOL indicators and domains, and that the majority of the tools demonstrate lack of proper coverage of QOL subdomains. The results also show wide variations in the number of indicators used and that most of the examined tools are using objective measurable indicators. The study has identified 67 indicators distributed across 13 domains that constitute the core criteria of the proposed QOL assessment tool. The selected indicators and domains cover all attributes of urban QOL and are evaluated by experts as important criteria to assess/measure QOL. Moreover, the results demonstrate the advantage of the developed framework and comprehensive list of criteria (CLC) as a structured and efficient approach to design better QOL assessment tools